IMPLEMENTATION OF DIGITAL MARKETING IN IMPROVING ROOM OCCUPANCY AT THE WESTIN RESORT & SPA, UBUD - I Putu Ade Perdana Putra; Ni Putu Lianda Ayu Puspita; Ni Luh Eka Armoni; Elvira Septevany (Sekolah Tinggi Pariwisata Mataram, 2022)
The purpose of this study was to determine the application of digital marketing applied by The Westin Resort & Spa, Ubud and the efforts made to increase room occupancy through digital marketing. Data collection methods used are observation, interviews, and documentation. The analytical technique used in this study is descriptive qualitative analysis used to describe the information obtained through interviews from the sales & marketing party and relate it to the theories that support the discussion related to the dimensions and indicators of digital marketing conducted by The Westin Resort & Spa, Ubud. The results show that the application of digital marketing at The Westin Resort & Spa, Ubud is divided into four digital marketing dimensions, namely websites, online travel agents, social media, and Marriott Bonvoy. Besides, efforts are being made to increase room occupancy, namely, increasing brand awareness on social media by implementing a give away program every month.